1991
DOI: 10.1093/ndt/6.11.868
|View full text |Cite
|
Sign up to set email alerts
|

Haemodialysis Membranes Modulate Chronically the Production of TNF , IL1 and IL6

Abstract: As cytokines may play a role in the adverse effects of haemodialysis, TNF alpha, IL1 beta and IL6 were investigated before the haemodialysis session (chronic effect) and after 30 and 60 min (session effect). We found that haemodialysis exerts a chronic effect on cytokines but the type of haemodialysis membrane, Cuprophan or Hemophan, specifically influences each cytokine. Circulating levels of TNF and unstimulated production of TNF and IL1 by monocytes were increased in patients dialysed with Hemophan, whereas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
9
0

Year Published

1993
1993
2002
2002

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 0 publications
9
9
0
Order By: Relevance
“…Our study confirms the findings of several other studies which have reported greater than normal T N Fa production by mononuclear cells pre-HD [9,11,[19][20][21], Some of these studies like ours found a further increase in spontaneous TN Fa production immediately post-HD with cellulosic (Cuprophan) but not synthetic dialysis membranes [9,21]. Also in agreement with our findings most studies did not find an increase in TN Fa production with LPS stimulation after HD compared to pre-HD [9,11,19], although in the study of Chollet-Martin et al [9] this depended on the type of dialysis membrane.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our study confirms the findings of several other studies which have reported greater than normal T N Fa production by mononuclear cells pre-HD [9,11,[19][20][21], Some of these studies like ours found a further increase in spontaneous TN Fa production immediately post-HD with cellulosic (Cuprophan) but not synthetic dialysis membranes [9,21]. Also in agreement with our findings most studies did not find an increase in TN Fa production with LPS stimulation after HD compared to pre-HD [9,11,19], although in the study of Chollet-Martin et al [9] this depended on the type of dialysis membrane.…”
Section: Discussionsupporting
confidence: 93%
“…It has been shown that the pluripotent cytokine interleukin 1 (1 L-l) can be released after contact with dialysis membranes both in vitro [1][2][3] and in vivo [4,5]. Plasma levels of three proinflammatory cytokines IL-1, interleukin-6 (IL-6) and tumor ne crosis factor a (TNFa) have been reported to be increased in HD patients although there is controversy as to whether short-term changes occur during the HD procedure itself [4][5][6][7][8][9][10][11], This study was done to assess both the production of TN Fa by mononuclear cells from HD patients and the effect of the dialysis treatment itself on TN Fa production. Since endogenous serum factors such as complement and exogenous factors such as endotoxin fragments might cross Accepted ; September the HD membrane and contribute to TN Fa production, spontaneous TN Fa production by cells of HD patients was examined both in their own sera and in non-HD sera.…”
Section: Introductionmentioning
confidence: 99%
“…We confirmed our previous observations as well as those of others [17][18][19] that both pre-and post-HD PBMC produced significantly more TN Fa activity than the PBMC of normal controls. In addi tion we found that PBMC from HD patients produced significantly more TN Fa than PBMC from uremic patients not on dialysis who had TN Fa activity similar to that of controls.…”
Section: Discussionsupporting
confidence: 93%
“…Similar results were obtained for TNF [102,103] and IL-6 [104,105]. An IL-6 production (related to beta-2-microglobulin release) was observed, by our group, both before and after dialysis treatment with cellulosic membranes, suggesting a chronic or prolonged PBMC stimulation [106].…”
Section: Cytokine Production By Cultured Pbmcsupporting
confidence: 81%